A new Vincetoxicum (Apocynaceae) species from Eastern Anatolia and its relationship based on biosystematic properties. (26th November 2021) - Güven, Seher; Coşkunçelebi, Kamil; Makbul, Serdar
Abstract : Vincetoxicum anatolicum (Apocynaceae), a new species from eastern Turkey, is described and illustrated. Additionally, a revised key for Turkish Vincetoxicum is provided and the seed micromorphology and palynological properties of the new species is described for the first time. The new species is morphologically similar to V. fuscatum and V. parviflorum, but it can be distinguished by its 8–12 mm long peduncles, yellow to light brown corolla with crisped hairs on the inner surface, and ovate corona segments partly fused with intermediate teeth, as well as by palynological properties like obovate pollinia and rugulate exine sculpture. However, phylogenetic analyses showed that the new species, attributed to the ' Vincetoxicum s.str. clade', is clustered in the same subclade as V. funebre, V. rehmannii and V. scandens rather than with the species morphologically most similar to it.